A STUDY OF ACCOUNTING STUDENTS' PERCEPTION TOWARDS THE PROFESSIONALISM OF ACCOUNTING LECTURERS IN UNIVERSITIES IN JEMBER REGENCY - Syarofah, Hani Fatus; Yulinartati; Suharsono, Riyanto Setiawan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze students' perceptions of the professionalism of accounting lecturers at higher education institutions in Jember Regency, focusing on three main variables: knowledge, skill, and attitude. Data were collected through an online questionnaire distributed to 79 students from four universities. The data were analyzed using multiple linear regression with the help of SPSS version 30. The results show that the variables of knowledge and attitude have a significant influence on lecturer professionalism, while the skill variable does not have a significant impact. The Adjusted R² value of 19.9% indicates that the model explains only a small portion of the variability in student perceptions, with the remaining variation influenced by other factors not included in this study. This research contributes to understanding the key factors that affect students' perceptions of lecturer professionalism, particularly in accounting education. The study's limitations include a narrow geographical scope and the absence of direct observation. Future research is recommended to broaden the population and consider additional variables to achieve more comprehensive results. Practically, the findings highlight the importance of improving lecturers' knowledge and professional ethics to enhance the overall learning experience for students.